Chronic pain is independently associated with social frailty in community‐dwelling older adults. Issue 11 (23rd October 2019) - Hirase, Tatsuya; Makizako, Hyuma; Okubo, Yoshiro; Lord, Stephen R; Inokuchi, Shigeru; Okita, Minoru
Abstract : Aim: The present study aimed to determine whether measures of chronic pain are associated with social frailty in community‐dwelling older adults. Methods: Participants comprised 248 older adults who enrolled for community‐based exercise classes. Chronic pain was defined as the presence of significant pain‐related symptoms within the past month that had continued for at least 6 months. Social frailty was defined as positive responses to two of the following five questions (going out less frequently, rarely visiting friends, feeling unhelpful to friends or family, living alone and not talking with someone every day). Physical function was assessed using the Chair Stand and Timed Up and Go tests. Results: A total of 55 participants (22.2%) met the criteria for social frailty. A total of 28 socially frail participants (50.9%) and 56 of the socially integrated participants (29.0%) reported chronic pain. The presence of chronic pain was significantly associated with social frailty after adjusting for age, sex and physical function measures (odds ratio 2.13, 95% confidence interval 1.01–4.48). Chronic pain was also significantly associated with three social frailty items: going out less frequently, rarely visiting friends and feeling unhelpful to friends or family. Conclusions: Chronic pain was independently associated with social frailty in community‐dwelling older adults. Simple assessments of chronic pain and subsequent pain management interventions might be beneficial for older people with social frailty. Geriatr Gerontol Int 2019; 19: 1153–1156 .